INCREASING KNOWLEDGE ABOUT ORAL CARE AMONG ELEMENTARY STUDENTS IN SDN DUKUHSARI 2 JABON SIDOARJO - Diana, Meli; Qiromah, Nafidatul; Maharani, Calista; Maulani, Vitta; Nimreksu, Felicia; Oratmangun, Maria; Alfiyan; Afriyanto (Community Service Journal of Indonesia, 2023)
This community service activity carried out by Poltekkes Kerta Cendekia is routine activities done by academic civities in order to improve the health quality of school-age children in the Sidoarjo Regency environment. This activity carries the theme "Oral Care". Increasing the level of knowledge, attitudes, and skills of students regarding oral and dental health will change their behavior towards healthy living so that optimal dental and oral health degrees can be achieved. The long-term impact of this activity is that by improving the health quality of students, it is hoped that they can improve their academic achievement. This counseling activity was held on January 21, 2023, at SDN Dukuhsari 2 Jabon Sidoarjo. This activity was carried out by a team consisting of one lecturer and seven students. The participants in this activity were all 1st and 2nd graders at this elementary school, which totaled 39 students. During this activity, all students could work well together, were enthusiastic in answering all the questions posed by the presenters, and were enthusiastic in demonstrating how to brush their teeth.